The Effect Of Back Massage Therapy On Sleep Quality Of The Elderly At The Puskesmas Tanjung Medan, Labuhan Batu Selatan Regency In 2021 - Fitriani Fadillah (Science Midwifery, 2021)
Massage has many benefits on the human body system such as reducing muscle pain, on the cardiovascular system can increase circulation and stimulate blood flow throughout the body, can also stimulate skin cell regeneration and help in the body's barrier, as well as its effect on the nervous system canreduce the risk of impaired sleep quality.The purpose of this study was to determine the effect of back massage therapy on sleep quality in the elderly at the Tanjung Medan Health Center in 2022. This type of research is a quantitative study with pre-experimental research methods.The population in this study were all children who were circumcised in August in theFathiyah Husada Medical Center. Sampling technique withpurposive sampling, the number of samples as many as 15 people. The instrument used is the questionnaire sheetfamily sleep qualityand observation sheets, namely SOP) Standard Operating Procedures. Data analysis was carried out with univariate and bivariate using the Wilcoxon test. The results of the study thatSupport SystemGood families reach 12 families (57.1%), therefore the majority in the Family Support System are "Good". Child's anxiety levelmild majority as many as 9 respondents (42.9%). Statistical test results with Wilcoxon's test Back Massage Therapy on Sleep Quality in the ElderlyinTanjung Medan Health Center in 2022value is obtained. of 0.05. The conclusions of the research are:The Effect of Back Massage Therapy on Sleep Quality in the Elderly at Tanjung Medan Health Center in 2022. It is hoped that the research site will further improve the quality of service and maintain it.